Gene expression profiling in melanoma: past results and future potential. (20th November 2018) - Knackstedt, Rebecca W; Knackstedt, Thomas; Gastman, Brian
The field of melanoma oncology is rapidly evolving with advances in detection, staging and treatment. There is heterogeneity in all stages of melanoma where some patients fare better than others for reasons currently unknown and it is sometimes unclear which patients warrant closer surveillance, multidisciplinary care, increased imaging, more aggressive surgery or adjuvant therapy. Early studies have shown the predictive ability of gene expression profiling (GEP) and institutions that have adopted GEP for melanoma treatment have demonstrated changes in practice patterns and patient management. The goal of this paper is to review the clinical evidence for a new diagnostic test, DecisionDx-Melanoma, the only GEP test for cutaneous melanoma with prospective studies analyzing its utility.